Assessment of route and destination displays on public service vehicles. Part 4: conclusions and recommendations. - Sharon Cook; Clare Lawton (2004)
The previous reports associated with this research project have related to specific areas of research: · Part one – Research review and industry consultation · Part two – Laboratory trials · Part three – Field trials. The aim of this report is to draw conclusions from these findings and develop recommendations.